Patterns of export shipments. Issue 2 (25th February 2022) - Yang, Xuebing
Abstract : Purpose: This paper studies the frequency and the average size of export shipments at the firm–product–destination level. Design/methodology/approach: This paper sets up a theoretical model about the shipping frequency and the shipment size of exports to a given market from individual exporters. Then it confronts the predictions of the model with trade data. Findings: This paper shows that patterns of export shipments are determined by (1) a product's export potential in a market, which is the exports revenue when the firm delivers the exports of the product to the market in a single shipment in each period; and (2) factors related to the firm's efficiency of managing shipments of the product exported to the market. Originality/value: This paper reveals some important patterns of export shipments. It provides a theoretical model that explains the patterns.